Factors That Influence Consumer Satisfaction Using Seven One Hotel Lodging Manna South Bengkulu - Putra, M. Sendika Martha Dwi Putra; Hanila, Siti; Zoniarti, Zoniarti (Tractare: Jurnal Ekonomi-Manajemen, 2024)
Marketing activities are crucial for the hospitality industry, as hotels provide complex services and facilities available 24 hours a day. Hotels support business travelers and tourists in need of accommodation, food, drinks, and entertainment during their stays. This research employs a quantitative approach, utilizing methods such as Validity Testing, Reliability Testing, Multiple Linear Regression Analysis, Coefficient of Determination, and hypothesis testing through t-test. The study involved 62 visitors to Hotel Seven One in South Manna, South Bengkulu. The Multiple Linear Regression Analysis results in the equation Y = 5.805 +0.160 X1 + 0.338X2 + 0.148X3 + 0.073 X4 + 0.181 X4, indicating a positive regression direction. The physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) factors have a positive influence on customer satisfaction (Y) at Hotel Seven One in Manna, South Bengkulu. The coefficient of determination value, calculated using SPSS, is R-squared at 0.961. This suggests that the physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) collectively influence customer satisfaction (Y) by 96.1%, with the remaining 3.9% affected by unexamined variables. The t-test results at a significance level of 0.05 show that individual X variables significantly impact Y at Hotel Seven One in Manna, South Bengkulu.